1971
DOI: 10.1083/jcb.49.2.288
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Endoplasmic Reticulum in Hepatocytes

Abstract: Electron microscope cytochemical localization of glucose-6-phosphatase in the developing hepatocytes of fetal and newborn rats indicates that the enzyme appears simultaneously in all the rough endoplasmic reticulum of a cell, although asynchronously within the hepatocyte population as a whole . To confirm that the pattern of cytochemical deposits reflects the actual distribution of enzyme sites, a method to subfractionate rough endoplasmic reticulum was developed . The procedure is based on the retention of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

1972
1972
2001
2001

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(38 citation statements)
references
References 22 publications
3
35
0
Order By: Relevance
“…In contrast, the density alteration described in this and other (8,19,25) papers is performed in vitro on subcellular organelles whose equilibrium density is initially unaffected.…”
Section: Analytical and Preparative Applications To Subcellular Organmentioning
confidence: 93%
“…In contrast, the density alteration described in this and other (8,19,25) papers is performed in vitro on subcellular organelles whose equilibrium density is initially unaffected.…”
Section: Analytical and Preparative Applications To Subcellular Organmentioning
confidence: 93%
“…It should, however, be borne in mind that the absence of visible deposits in many vesicles does not mean that these vesicles are devoid of either deposit or glucose 6-phosphatase activity, since deposits may have been missed in the particular plane in which the vesicles are sectioned. Leskes et al (1971b), using a much higher Pb(N03)2 concentration in the incubation medium, also found vesicles that contained no deposit. The specific activities of glucose 6-phosphatase in the bands obtained by the technique described in this paper are given in Tables 2 and 3.…”
Section: Explanation Of Platementioning
confidence: 99%
“…During the development of this technique, Leskes et al (1971b) published their, rather different, procedure for separating microsomal vesicles containing glucose 6-phosphatase from those devoid of such activity. Our method is also of general applicability and can be used, for example, to separate vesicles derived from the endoplasmic reticulum from plasma membrane, Golgi elements and other components of the microsomal fraction as well as separating vesicles containing different amounts of glucose 6-phosphatase activity.…”
mentioning
confidence: 99%
“…The lack of glucose accumulation indicates that G1P is transported into vesicles lacking G6Pase enzyme activity, since G1P is a good substrate for the G6Pase enzyme [26]. Classic reports on the localization of the G6Pase enzyme activity in liver ER in situ [29], and in isolated liver microsomal vesicles [30], indicated that the enzyme is not present in all vesicles, even though it is evenly distributed throughout the entire ER network. In liver, GPT activity is therefore probably not involved in G6P hydrolysis by the G-6-Pase enzyme.…”
Section: Discussionmentioning
confidence: 99%